Determination of electricity quality indicators in distribution networks of industrial enterprises when using starting devices of powerful electric drives - Gromovyy, Oleksiy; Arailym, Smail; Karshiga, Smagulova; Mirkomil, Melikuziev; Baranovska, Mila; Romanets, Andrii; Novitsky, Ihor; Humeniuk, Anna; Kolysnychenko, Ilya; Bilukhin, Dmytro (Technology audit and production reserves, 2026)
The object of research is the processes of electromagnetic transformation in powerful asynchronous electric drives during controlled start-up and their impact on the quality of electricity in the power supply network. Distribution networks of industrial enterprises are considered, which have significant dynamic loads during the start-up of powerful machines. The problem to which the research is aimed is to ensure proper quality of electricity in distribution networks of industrial enterprises when performing controlled start-up of powerful asynchronous electric drives from soft starters based on a thyristor voltage regulator. Quantitative indicators of the influence of starting devices on the parameters of electricity quality were calculated using computer modeling in the MATLAB/Simulink environment. Soft start using a thyristor regulator, although it limits the starting current, has a negative impact on the quality of electricity in the distribution network. Reactive power consumption increases, which causes a voltage drop. For the case of starting an asynchronous motor with a capacity of 3500 kW in the network of a sintering factory, it was found that direct start causes a voltage drop of about 350 V. Harmonic voltage distortions with a distortion factor of up to 6% also appear. Power active filters allow to improve the quality of electricity by introducing antiphase currents, which is proven by the application of theoretical methods of electrical engineering. The results obtained are applicable in the design of electric drive systems of powerful mechanisms during the modernization of the power supply of industrial enterprises, in the calculation of reactive power compensation means and in the development of energy quality standards. This will significantly contribute to increasing the reliability of technological equipment, reducing energy losses, and increasing the service life of electrical equipment at the enterprise.